(untitled) (Global Journal of Human-Social Science, 2021)
Employment generation in Nigeria is a welcome phenomenon as alleviating poverty and increasing economic activities to gain economic growth. It is the opposite of unemployment that has a devastating effect on the Nigerian economy. Nigeria’s unemployment situation has increased with its attendant consequences of high social vices, enlarged poverty; under-utilisation of human capacity; social alienation, and weak Naira purchasing power. At different times, Nigeria’s government put policies and programmes to solve unemployment, but no meaningful achievement is seen so far. It was deduced that most of Nigeria’s established programs to fight against unemployment could not achieve their desired and expected results. Using secondary data, we recommend, among other things, that the agricultural sector be improved upon to create employment and reduce unemployment in Nigeria. The public and private sectors should join hands in their quests in reducing unemployment and embark on Entrepreneurial development; self-employment training and etcetera is encouraged.